Using Genre-based Approach to Teach Business Email Writing in a Vietnamese University: Making Complaints - Lan Mai (Vietnam Journal of Education)
To equip students with necessary skills to join the global labor force, various ESP/ EOP courses have been provided in Vietnamese universities aiming at enhancing students’ business correspondence writing ability. As part of such an attempt, this action research study employs genre-based approach in teaching EFL business writing and investigates its effectiveness. Particularly, a system of moves and steps was utilised in the modelling stage to reinforce the generic structure of students’ complaint emails. Data were collected through pre-test, middle test, post-test and a questionnaire to assess students’ writing progress and their attitudes toward the teaching approach. The results show that the genre-based approach fosters students’ writing competency, the teaching moves and steps support them to better grasp the target mail’s structure. The students also made better choices of linguistic features in writing though they still needed more time to express their ideas really flexibly. The findings also highlight students’ positive reactions to the genre-based approach application. This study provides compelling evidence for both the pedagogical value of this approach and areas requiring continued attention in EFL writing instruction.